Glomus Tumor, a case report - Molina-Piedra, Dana (2024)
Glomus Tumor is a rare condition and in a high percentage of cases due to misdiagnosis by angiologists and orthopedists, its treatment is delayed. We present a case of Glomus Tumor in a 53- year-old white female patient with a history of Raynaud`s disease approximately 8 years ago. The clinical findings of the case and the evolution until surgical intervention are described.